(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Realism in literature has been a popular genre for centuries, with notable authors such as Eugène Marin Labiche and Émile Augier in France. However, critics argue that realism is not always truly representative of reality, as our perceptions and memories often distort the truth. Additionally, some scholars believe that the genre’s self-imposed limits can lead to a lack of objective truth. Others argue that there is no fixed definition of realism, making it an indispensable term in literary discourse. Despite these criticisms, realism remains a popular and important genre in literature.